Exploring learners' engagement with literacy in a book club - Jamieson, Vuyokazi (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning)
This study observes the literacy engagement of a group of learners enrolled in Grades 8"“10 in Nombulelo High School, a poorly-resourced school in the city of Makhanda in the Eastern Cape, South Africa. The learners participated in a book club hosted and run by St Andrew's College, a privileged independent school, as a community engagement initiative. The idea of extending literacy engagement and engagement with written texts beyond textbooks used in schools is critical for learners with ambitions to enter higher education. Studying at a university requires a lot of reading, and if reading has not been taken up as a practice that involves more than 'text consulting' (Geisler, 1994) students will be unlikely to read the number of texts required of them. Studies (see Geisler, 1994 for an overview) have shown how the literacy of the university is very different to school based literacies. The assumption behind the study on which this thesis reports is that engagement with fictional texts might promote reading and bring about understandings of this activity as enjoyable and not a task only associated with schooling. The study is underpinned by a critical realist philosophy which allowed for the identification of structures and mechanisms that led to the emergence of literacy events in learners' lives and to their experiences and observations of those events. The study was guided by the following questions: How do learners from a poorly-resourced high school engage around fictional texts in the context of a book club? What enables or constrains this engagement? The study was impacted by the Covid-19 pandemic in that lockdown requirements meant that learners from St Andrew's College could not participate in the book club as much as anticipated initially as they had been forced to return home to pursue online learning. Learners from Nombuelo High School were, however, granted access to College premises, where they met in the school library following strict Covid protocols. The study draws on in-depth interviews, observations and document analysis of five learners from Nombulelo High School who participated in the book club, as well as on book reviews they wrote for the book club website. The critical realist analysis allows for the identification of mechanisms in learners' homes and communities that enable literacies, including those that are screen-based such as using a computer, mobile phones and other technologies. This study found evidence of challenges regarding school based texts, reading fictional texts and viewing it as an enrichment of the school project. Because of children were African the emergence of communal practices and story telling is woven throughout the results section. However, is an example of the complexity of social and economic challenges facing South African marginalised schools.
Keywords: Book clubs (Discussion groups) -- South Africa -- Makhanda; Literacy -- South Africa -- Makhanda; High school students Books and reading -- South Africa -- Makhanda; Books and reading -- South Africa -- Makhanda; Reading, Psychology of; Service learning -- South Africa -- Makhanda; Critical realism